(3GdZQI GdLdjI aj TQM GdOQI GdHgjIs - (3GdcGTGfj, eMeO GdcGTGfj, eMeO Hf Ydj Hf eMeO, cGf MkjG (B1243(3g` (B1826(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj enqf YdjfG HQCaJg (B... (3jbhd QGLj GdQH Pj GdEMSGf (B*** (3Ydj Hf GdMSf GdBQGfjs
(3BNQgG (B:s
(3BNQgG(B: (3GdfLhe hGdGSJNGQI hGdbQYI hfMh Pdc eeG dG eONd dg aj GSJfHGW GdCMcGe GdTQYjI (B... (3GdTjYI GdEeGejI bO jchf MLI hEf CaGO GdXf HGdhGbYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 537s
(3GdPQjYI, L (B16: 25s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs